2014
DOI: 10.1021/jm501035j
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Screening of the Bromodomain of ATAD2

Abstract: Cellular and genetic evidence suggest that inhibition of ATAD2 could be a useful strategy to treat several types of cancer. To discover small-molecule inhibitors of the bromodomain of ATAD2, we used a fragment-based approach. Fragment hits were identified using NMR spectroscopy, and ATAD2 was crystallized with three of the hits identified in the fragment screen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 18 publications
8
77
0
Order By: Relevance
“…However, for BRPF1B, the displacement of W1 was predicted to carry a large free energy penalty of about 1 kcal mol −1 . Harner et al 9 showed instead how W4 could be displaced from ATAD2 by a fragment containing an aminothiazole group (fragment 12; PDB-ID 4TZ8). W4 was indeed predicted to be the second least stable site in ATAD2.…”
Section: General Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for BRPF1B, the displacement of W1 was predicted to carry a large free energy penalty of about 1 kcal mol −1 . Harner et al 9 showed instead how W4 could be displaced from ATAD2 by a fragment containing an aminothiazole group (fragment 12; PDB-ID 4TZ8). W4 was indeed predicted to be the second least stable site in ATAD2.…”
Section: General Approachmentioning
confidence: 99%
“…Recent studies have reported the complete or partial displacement of this four-water network. In 2014, Harner et al 9 reported the discovery an aniline-containing tricyclic fragment that was shown to bind deep into ATAD2, displacing all four conserved water molecules. In 2015, Fedorov et al 10 reported the displacement of all four conserved waters by salicylic acid from the binding pockets of a number of Family VIII bromodomains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Equally encouraging are inhibitors that have now been identified for more difficult to drug bromodomains, 18 such as BAZ2B 19, 20 and ATAD2A. 21-23 Unlike the BET sub-family, which contain two bromodomains that primarily drive their binding and therefore function, a large proportion of the other BCPs contain auxiliary domains, many with diverse and sometimes unknown functions. These multi-domain containing BCPs can also be part of multi-protein complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Since at early stages of the discovery process, FBDD is principally a hit-finding activity, it is beneficial that the protein is uniformly labeled. If protein supply is not limiting, fragment-based approaches can be applied on an unconventionally large scale, as illustrated by a study describing the discovery of smallmolecule inhibitors of the bromodomain of ATAD2 (Harner, Chauder, Phan, & Fesik, 2014). The authors screened a library of approximately 13,800 fragments (in mixtures of 12) by protein observation using uniformly 15 N-labeled bromodomain of ATAD2.…”
Section: Applications In Drug Discoverymentioning
confidence: 99%